Community Empowerment Through Assistance in the Management of Cultural Tourism Products (Batik): Pemberdayaan Masyarakat Melalui Pendampingan Tata Kelola Produk Wisata Budaya (Batik) - Yulia Nurendah; Ani Mekaniwati; Tarida Marlin Surya Manurung (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The community service collaboration program between IBI Unity (IBIK) and Mara Technology University (UiTM) and Cibuluh Batik Village has been carried out through training activities for the Cibuluh Batik Village MSME group. In this activity, it was found that the UMKM group in Kampung Batik Cibuluh was still experiencing problems in terms of streamlining production costs through suppressing production raw material costs and the inability of business actors to use available technological resources such as social media and online shopping applications (e-commerce). This activity was carried out to help residents of Kampung Batik Cibuluh as one of the MSME groups in solving their problems, especially in terms of determining production costs and marketing products digitally. Based on a survey on the effectiveness of MSME governance and the training conducted, the results obtained were that most business actors were parents and did not have sufficient experience which was the main reason for the implementation of production cost calculations that had not been maximized. In addition, problems related to digital marketing still require further training.